A study on service quality towards customer satisfaction / Nurul Syamihah Mohamad Royani - Mohamad Royani, Nurul Syamihah (Faculty of Business and Management, 2016)
Service quality and customer satisfaction are very important to a company which helps to run, increase loyalty, increase profit and improve the business of the company. This thesis presents a study, in which initiative is being made in improving service quality and customer satisfaction of MPWS Rich Resources Sdn Bhd. This is because there was no investigation conducted to analyze the satisfaction of the customers of the company. In theory, parts are described five determinants of good service quality which are reliability, assurance, responsiveness, empathy, and tangibles. The intention of the research study was to find out the relationship between service quality and customer satisfaction of MPWS Rich Resources Sdn Bhd. This research entitled “A Study on Service Quality towards Customer Satisfaction” had been conducted to obtain results and findings. There are 50 of respondents has answered the questionnaire. In addition, other sources of data also have been using as a referral to strengthen the issues in the research study. This research concludes with a discussion on these results, study limitation and recommendation to the company and future research directions.